Who IS This Woman, Anyway?- Hildegard Interpreted in the Twenty-First Century - Cameron, Cynthia (Lumen et Vita, 2013)
The last fifty years has seen a resurgence of interest in Hildegard of Bingen, a twelfth-century mystic, theologian, and nun. As her story is taken up by various scholars, the image of Hildegard that is presented tells us as much about the scholars as it tells us about Hildegard. By isolating two scholars who take Hildegard’s work seriously, we can investigate the ways that the interpreter can shape what they find in a historical source for a particular theological purpose. Barbara Newman and Pope Benedict XVI approach Hildegard from very different perspectives and the vision of Hildegard that they each present tells us as much about these scholars and their interests as they do about Hildegard hers